2023
DOI: 10.1109/jiot.2023.3267335
|View full text |Cite
|
Sign up to set email alerts
|

Multitask Deep Learning for Human Activity, Speed, and Body Weight Estimation Using Commercial Smart Insoles

Abstract: Healthcare professionals and individual users use wearable devices equipped with various sensors for healthcare management. Recently, the joint usage of artificial intelligence and these wearable sensors has played an essential role in healthcare management by providing a wide range of applications such as fitness tracking, gym activity monitoring, patient rehabilitation monitoring, and disease detection. These tasks eventually aim to enhance personal well-being and better manage the user's physical health by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that these devices accurately measure changes in plantar pressure during walking [ 21 ]. Additionally, it has been revealed that they can be utilized for real-time walking speed estimation, weight estimation, and activity classification [ 12 ]. For this study, we obtained a program from the manufacturer to receive real-time plantar pressure data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that these devices accurately measure changes in plantar pressure during walking [ 21 ]. Additionally, it has been revealed that they can be utilized for real-time walking speed estimation, weight estimation, and activity classification [ 12 ]. For this study, we obtained a program from the manufacturer to receive real-time plantar pressure data.…”
Section: Methodsmentioning
confidence: 99%
“…Smart insoles capable of capturing real-time measurements of plantar pressure during everyday activities have been introduced and made available in the market at reasonable prices [ 12 , 13 ]. Since the inception of smart insoles, numerous studies have explored their applications in the medical field.…”
Section: Introductionmentioning
confidence: 99%
“…compared to the MAE of 15.10 lbs. achieved by Kim et al in [10]. This is because the pro- Table 6 illustrates the performance analysis of the proposed method on both the environmental settings with respect to the existing state-of-the-art method.…”
Section: Balancedmentioning
confidence: 97%
“…achieved by Kim et al in [10]. This is because the proposed method generates a personalized model for every participant rather than using the whole dataset to train a single machine learning model as performed in [10].…”
Section: Balancedmentioning
confidence: 99%
See 1 more Smart Citation